1998
DOI: 10.1172/jci870
|View full text |Cite
|
Sign up to set email alerts
|

Increased sphingomyelin content of plasma lipoproteins in apolipoprotein E knockout mice reflects combined production and catabolic defects and enhances reactivity with mammalian sphingomyelinase.

Abstract: Apolipoprotein E knockout (apoE0) mice accumulate atherogenic remnant lipoproteins in plasma. We now provide evidence that these particles are enriched in sphingomyelin (SM), and explore the mechanisms and possible pathophysiological consequences of this finding. The phosphatidylcholine/sphingomyelin (PC/SM) ratio was reduced in all lipoproteins in apoE0 mice compared with wild-type (Wt) mice (2.0+/-0.2 vs. 4.7+/-0.5; 2.8+/-0.5 vs. 5.5+/-0.9; 1.9+/-0. 5 vs. 4.6+/-0.5 for VLDL, LDL, and HDL), reflecting 400 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
112
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 45 publications
9
112
0
Order By: Relevance
“…11 The concentration of SM relative to total phospholipids (principally phosphatidylcholine [PC] and SM), ie, SM/(SMϩPC), is an important determinant of the susceptibility of lipoprotein SM to SMase. 8,12 These findings suggest that plasma SM levels and the relative SM concentration might be risk factors for atherosclerosis. However, plasma SM levels have never been systematically assessed as a risk factor for atherosclerosis in humans.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…11 The concentration of SM relative to total phospholipids (principally phosphatidylcholine [PC] and SM), ie, SM/(SMϩPC), is an important determinant of the susceptibility of lipoprotein SM to SMase. 8,12 These findings suggest that plasma SM levels and the relative SM concentration might be risk factors for atherosclerosis. However, plasma SM levels have never been systematically assessed as a risk factor for atherosclerosis in humans.…”
mentioning
confidence: 86%
“…In addition, the OR for CAD for the relative concentration of SM, ie, the SM/(SMϩPC) ratio, was significantly higher for the third and fourth quartiles compared with the first quartile (Pϭ0.0218 and Pϭ0.0028, respectively), indicating that the relative concentration of SM was also associated with CAD, independent of age, diabetes, smoking, hypertension, LDL-C, HDL-C, logarithmically transformed triglycerides, remnant cholesterol, fibrinogen, and CRP (Table 3). 11,12,21 has suggested that plasma SM levels could also be related to atherosclerosis. However, this has never been systematically assessed, partly because of the difficulties of measuring SM in large numbers of samples.…”
mentioning
confidence: 99%
“…Sphingolipid enrichment in vitro increased aggregation of mouse lipoproteins. Macrophage-derived SMase was also shown to stimulate the aggregation of very low density lipoproteins (VLDL) and LDL [12]. Thus, lipoprotein aggregation induced by SMase is dependent on ceramide increase.…”
Section: Lipoproteins and Ceramidementioning
confidence: 99%
“…Sphingomyelin, which is transported into the arterial wall by atherogenic lipoproteins, is in turn affected by arterial wall SMase, increasing in ceramide content and promoting lipoprotein aggregation [2]. LDL extracted from human atherosclerotic lesions is highly enriched in sphingomyelin compared with plasma LDL [12,13].…”
Section: Lipoproteins and Ceramidementioning
confidence: 99%
See 1 more Smart Citation